Targeting ASCT2-mediated glutamine metabolism inhibits proliferation and promotes apoptosis of pancreatic cancer cells. Issue 3 (31st March 2022) - Wang, Wenbin; Pan, Haihua; Ren, Feihua; Chen, Hongxia; Ren, Ping
Abstract: Some tumor cells have a high rate of glutamine uptake and exhibit glutamine addiction. Alanine-serine cysteine-preferring transporter 2 (ASCT2) is a major mediator of glutamine supply in many tumor cells, but the underlying effects and mechanisms of ASCT2 in pancreatic cancer (PC) are largely unknown. Our results show that ASCT2 expression is significantly higher in PC than in normal pancreatic duct cells and pancreas. Utilizing the Kaplan–Meier Plotter database, a high expression of SLC1A5 mRNA was significantly associated with poor overall survival (OS) in patients with PC. shRNA-mediated inhibition of ASCT2 function in vitro can significantly decrease glutamine consumption, α-ketoglutarate (α-KG) production and ATP generation and increase the reactive oxygen species (ROS) level. Moreover, the antioxidant N-acetylcysteine partially attenuated the increase in the ROS levels and reduced ATP generation. These data suggest that ASCT2 mediates glutamine metabolism and maintains redox homeostasis in PC. To further investigate whether ASCT2 is involved in PC cell growth, we blocked ASCT2 activity with the ASCT2 inhibitor l -γ-glutamyl- p -nitroanilide (GPNA) and silenced the expression of ASCT2 with specific shRNAs. We found that the growth of PC cells was significantly inhibited. Additionally, knockdown of ASCT2 induced apoptosis through the Akt/mTOR signaling pathway. Furthermore, the loss of ASCT2 in BxPC-3 cell xenografts significantly inhibited tumor growth in vivo, and this effect was associated with an increase in cleaved caspase-3 expression and a decrease in Ki67 staining. Taken together, our results show that ASCT2 may be utilized as a putative therapeutic target for PC.